Minimally invasive fetal therapy for hydropic lung masses: three different approaches and review of the literature. (12th September 2013) - Baud, D.; Windrim, R.; Kachura, J. R.; Jefferies, A.; Pantazi, S.; Shah, P.; Langer, J. C.; Forsey, J.; Chaturvedi, R. R.; Jaeggi, E.; Keating, S.; Chiu, P.; et al.
ABSTRACT Objective To report three different antenatal therapeutic approaches for fetal lung masses associated with hydrops. Methods Three prospectively followed cases are described, and all 30 previously published minimally invasive cases of fetal therapy for hydropic lung masses are reviewed. Results Three hydropic fetuses with large intrathoracic lung masses presented at 17, 25 and 21 weeks of gestation, respectively. An aortic feeding vessel was identified in each case and thus a bronchopulmonary sequestration (BPS) was suspected. Under ultrasound guidance, the feeding vessel was successfully occluded with interstitial laser (Case 1), radiofrequency ablation (RFA) (Case 2) and thrombogenic coil embolization (Case 3). Complete (Cases 1 and 2) or partial (Case 3) resolution of the lung mass and hydrops was observed. A healthy infant was born at term after laser therapy (Case 1), and the involved lung lobe was resected on day 2 of postnatal life. In Case 2, hydrops resolved completely following RFA, but an iatrogenic congenital diaphragmatic hernia and abdominal wall defect became apparent 4 weeks later. The neonate died from sepsis following spontaneous preterm labor at 33 weeks. In Case 3, despite technical success in complete vascular occlusion with coils, a stillbirth ensued 2 days after embolization. Conclusions The prognosis of large microcystic or echogenic fetal chest masses associated with hydrops is dismal. This has prompted attempts at treatment by open fetal surgery, with mixed results, high risk of premature labor and consequences for future pregnancies. We have demonstrated the possibility of improved outcome following ultrasound‐guided laser ablation of the systemic arterial supply. Despite technical success, RFA and coil embolization led to procedure‐related complications and need further evaluation. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.